Perovskite solar cell and manufacturing method thereof

The perovskite solar cell employs a laminated electrode structure with varying density layers to address inefficiencies in carbon black distribution, achieving low-resistance electrodes with reduced processing time and costs, and ensuring substrate stability.

JP2025008105APending Publication Date: 2025-01-20AISIN CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023109984
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for distributing carbon black near the contact surface of a CdTe film in solar cells are inefficient and costly, particularly when scaling to large-area glass substrates, and pose a risk of substrate breakage during centrifugation or ultrasonic vibration.

Method used

A perovskite solar cell design with a laminated electrode structure, comprising multiple layers of varying density, formed by applying a viscous material containing dispersed solid substances, specifically using carbon nanotubes with different densities to reduce contact resistance and electrode resistance.

Benefits of technology

The laminated electrode structure allows for a low-resistance carbon electrode to be manufactured simply and effectively, reducing processing time and costs while ensuring substrate integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008105000001_ABST
    Figure 2025008105000001_ABST
Patent Text Reader

Abstract

To provide a perovskite solar cell having a low-resistance carbon electrode that can be manufactured by a simple method, and a manufacturing method thereof.SOLUTION: A perovskite solar cell 10 includes an electrode 62 provided on the surface of a hole transport layer 5. The electrode 62 is formed by stacking a plurality of electrode layers 62a, 62b, each of which has a different density and is made of the same active material.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a perovskite solar cell and a method for producing the same. [Background technology]

[0002] Solar cells generally use elements such as silicon, compound semiconductors, and organic semiconductors, but perovskite solar cells have been attracting attention because of their high light-harvesting ability, as well as the possibility of making them thin films and reducing costs.

[0003] Patent Document 1 discloses a technique for increasing the weight ratio of carbon black to graphite in the vicinity of the contact surface of a carbon electrode containing graphite and carbon black with a CdTe film in a CdS / CdTe solar cell compared to other parts of the electrode. This reduces the resistance in the vicinity of the contact surface of the carbon electrode with the CdTe film and the contact resistance between the carbon electrode and the CdTe film without increasing the resistance of the electrode itself. In order to increase the weight ratio of carbon black to graphite, a carbon paste is applied to the CdTe film to form a coating film, and then the carbon black is unevenly distributed using centrifugation and / or ultrasonic vibration to increase the carbon black ratio in the vicinity of the contact surface between the carbon electrode and the CdTe film. This reduces the resistance in the vicinity of the contact surface and improves the photoelectric conversion efficiency. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-330506 Summary of the Invention [Problem to be solved by the invention]

[0005] By centrifugal separation or ultrasonic vibration, carbon black with a particle size of several tens of nm is filled between graphite particles with a particle size of several tens of μm, so that the carbon black is unevenly distributed near the contact surface between the carbon electrode and the CdTe film, and the carbon black ratio can be increased. However, for example, when forming a solar cell on a large-area glass substrate, it is very difficult in practice to apply a carbon paste and then use centrifugal separation or ultrasonic vibration to move the carbon black in the carbon paste to the vicinity of the CdTe film, and there is a problem that it is not profitable in terms of processing time and cost. In addition, there is a risk that the glass substrate will break when centrifugal separation or ultrasonic vibration is applied.

[0006] Therefore, there is a demand for a perovskite solar cell having a low-resistance carbon electrode that can be produced by a simple method, and a method for producing the same. [Means for solving the problem]

[0007] A characteristic feature of the perovskite solar cell according to the present invention is that it is a perovskite solar cell comprising an electrode provided on a surface of a hole transport layer, the electrode comprising a plurality of electrode layers stacked together, each of the plurality of electrode layers having a different density and made of the same active material.

[0008] A feature of the manufacturing method of the perovskite solar cell according to the present invention is that a viscous material in which solids are dispersed in a solvent is applied to the surface of a hole transport layer, thereby laminating a plurality of electrode layers with different densities to form electrodes.

[0009] For example, an electrode may be formed by forming a low-density electrode layer adjacent to the surface of the hole transport layer, and laminating a high-density electrode layer made of the same active material on the low-density electrode layer to a greater thickness than the low-density electrode layer, thereby reducing the contact resistance between the low-density electrode layer and the hole transport layer and reducing the resistance of the electrode itself.

[0010] This makes it possible to provide a perovskite solar cell having a low-resistance carbon electrode that can be produced by a simple method, and a method for producing the same. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view of a perovskite solar cell. [Diagram 2] FIG. 1 is a top perspective view of a perovskite solar cell. [Diagram 3] FIG. 1 is a cross-sectional view explaining the power generation principle of a perovskite solar cell. [Figure 4] FIG. 1 is an explanatory diagram showing a procedure for producing a perovskite solar cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of a perovskite solar cell 10 (hereinafter simply referred to as solar cell 10) using a hole transport material according to an embodiment of the present invention will be described with reference to the drawings. The solar cell 10 is configured to include a perovskite layer 44 made of an organic and inorganic hybrid compound. However, the solar cell 10 is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the invention.

[0013] [Basic structure of solar cell] As shown in FIG. 1 and FIG. 2, the solar cell 10 according to the present embodiment includes a substrate 2 and a laminate 11 provided on the substrate 2. The substrate 2 includes a transparent substrate 21 and a transparent conductive film 22. The laminate 11 includes a blocking layer 3, a power generation layer 4, and a hole transport layer 5. The blocking layer 3 is provided on the transparent conductive film 22, and transfers electrons to the transparent conductive film 22, and separates the hole transport layer 5 from the transparent conductive film 22 to prevent recombination of electrons and holes (reverse electron transfer). The power generation layer 4 is provided on the blocking layer 3, and is formed by laminating a perovskite layer 44, which is excited by light to generate electrons, on a porous semiconductor 41. The hole transport layer 5 is provided on the power generation layer 4, and holes generated in the perovskite layer 44 pass through the hole transport layer 5. In addition, a photoelectrode 61 that emits electrons through the transparent conductive film 22 is provided on the surface of the blocking layer 3, and a counter electrode 62 (an example of an electrode) that receives electrons is provided on the surface of the hole transport layer 5. The counter electrode 62 is formed from the surface of the hole transport layer 5, passing through the side surfaces of the hole transport layer 5 and the perovskite layer 44, and extending to the surface of the blocking layer 3. Hereinafter, the photoelectrode 61 and the counter electrode 62 will be collectively referred to as the electrode 6. The arrangement of the electrode 6 is not particularly limited as long as it allows the transfer of electrons; for example, the photoelectrode 61 may be formed by connecting a conductor to the transparent conductive film 22. In order to increase the durability of the solar cell 10, the counter electrode 62 may be protected by the transparent substrate 21 or the like.

[0014] The transparent substrate 21 is made of a material having optical transparency. Examples of the transparent substrate 21 include a transparent glass substrate, a frosted semi-transparent glass substrate, and a transparent resin substrate. Examples of the transparent conductive film 22 include fluorine-doped tin oxide (FTO), tin oxide (TO), tin-doped indium oxide (ITO), zinc oxide (ZnO), and aluminum-doped zinc oxide (AZO).

[0015] Metal oxides are suitable for the blocking layer 3 and the porous semiconductor 41, and titanium dioxide (TiO2), zinc oxide (ZnO), niobium oxide (Nb2O5), tin dioxide (SnO2), aluminum oxide (Al2O3), etc. are used. In particular, it is preferable to configure them as a sintered body of titanium dioxide (TiO2) that can secure a large surface area for stacking the perovskite layer 44. In addition, a part of the blocking layer 3 extends into a recess 221 formed by removing a part of the transparent conductive film 22 to form an insulating layer 31, which divides the transparent conductive film 22 into two. In the blocking layer 3, electrons can move in the stacking direction, but are difficult to move laterally perpendicular to the stacking direction. In addition, electrons cannot move between the two transparent conductive films 22 separated by the insulating layer 31. In other words, the electrons that enter the blocking layer 3 move smoothly in the stacking direction of the transparent conductive film 22 and are supplied to the photoelectrode 61, but the insulating layer 31 prevents them from moving laterally toward the counter electrode 62, so that the photoelectrode 61 and the counter electrode 62 are not short-circuited.

[0016] The perovskite layer 44 is produced by reacting a compound (PbX2, X = halogen element) composed of lead and halogen element X with methylammonium iodide (CH3NH3I: hereinafter sometimes abbreviated as "MAI"). Specifically, a solution containing lead and halogen element X (for example, a solution of PbI2 in N,N-dimethylformamide) is infiltrated into the pores of the porous semiconductor 41, dried, and then immersed in a mixed solution of MAI, whereby crystals of the perovskite compound (CH3NH3PbI3 when X = I) that forms the perovskite layer 44 are rapidly produced. Note that iodine, bromine, chlorine, etc. can be used as the halogen element X, and it is particularly preferable to use iodine, which has high morphological stability. Alternatively, the halogen element X may be a mixed cation-mixed halide ((FAPbI3)) using MABr and 0.2M lead bromide (PbBr2), or FAI and lead iodide (PbI2). 1-x (MAPbBr3) x ) can also be used. In this case, for example, (FAPbI3) 0.85 (MAPbBr3) 0.15 etc. can be suitably used.

[0017] The hole transport layer 5 uses a hole transport material described later. The photoelectrode 61 uses, for example, a simple metal or alloy such as gold, platinum, silver, or copper, or an oxide conductor such as fluorine-doped tin oxide (FTO) or tin-doped indium oxide (ITO). The counter electrode 62 uses carbon nanotubes (an example of an active material; hereinafter, sometimes abbreviated as CNT). CNTs are highly conductive and a fibrous continuum. As a continuum, the interparticle resistance is low, making it possible to reduce the resistance of the electrode itself.

[0018] Here, the principle of how the solar cell 10 generates electricity will be described with reference to Fig. 3. When light such as sunlight or indoor light is incident from the transparent substrate 21 side, this incident light is transmitted through the substrate 2 and the blocking layer 3 without being absorbed, and most of it reaches the power generation layer 4. When the incident light that has reached the power generation layer 4 is irradiated onto the perovskite layer 44, the perovskite layer 44 absorbs the light energy and becomes excited. When the energy level of the perovskite layer 44 becomes higher than the conduction band potential of the metal oxide that is the porous semiconductor 41 by a predetermined level or more due to this excitation, electrons are injected from the perovskite layer 44 into the porous semiconductor 41. The injected electrons pass through the blocking layer 3 and are collected by the photoelectrode 61.

[0019] On the other hand, holes generated in the perovskite layer 44 reach the counter electrode 62 via the hole transport layer 5, where they recombine with electrons that have passed through the external load 7. In other words, a potential gradient is generated between the photoelectrode 61 and the counter electrode 62, so that power can be supplied by connecting the external load 7 between the two electrodes.

[0020] [Solar cell fabrication procedure] Next, a procedure for producing the solar cell 10 according to this embodiment will be described with reference to FIG. 4. However, the present invention is not limited to the following embodiment, and various modifications are possible without departing from the spirit of the present invention. The solar cell 10 can be produced with reference to known techniques such as those described in Michael Saliba et al., “Correction to “How to Make over 20% Efficient Perovskite Solar Cells in Regular (nip) and Inverted (pin) Architectures”, Chem. Mater., 2018, 30, 4193-4218.

[0021] First, the transparent conductive film 22 is formed on the transparent substrate 21 to prepare the substrate 2. The transparent conductive film 22 is laminated on the transparent substrate 21 by, for example, CVD (chemical vapor deposition) or sputtering. Next, the transparent conductive film 22 is partially removed by laser scribing to form a recess 221 for the insulating layer 31, and then washed. Next, the blocking layer 3 is formed on the entire surface of the substrate 2 by ALD (atomic layer deposition) or SPD (spray pyrolysis). The blocking layer 3 is preferably formed as a TiO2 dense layer. Next, a porous semiconductor 41, which is a nanoparticle sintered layer, is formed near the center on the masked substrate 2 and blocking layer 3. The porous semiconductor 41 is preferably formed as a porous layer of TiO2 (p-TiO2). This porous semiconductor 41 is formed by diluting the nanoparticle paste with a solvent, applying it by spin coating at a rotation speed of, for example, 4000 rpm to 6000 rpm, drying it, removing the masking, and heating it at 450° C. to 550° C. to sinter it.

[0022] Next, for example, a solution of PbI2 in N,N-dimethylformamide is prepared and dropped onto the porous semiconductor 41, after which the solution is permeated into the pores (p-TiO2) and excess solution is removed by spin coating at a rotation speed of, for example, 5000 rpm to 8000 rpm. The solution is then dried at 60°C to 120°C (preferably 70°C to 90°C) to form a PbI2 layer.

[0023] The substrate 2, blocking layer 3, and porous semiconductor 41 infiltrated with lead iodide are immersed in an isopropyl alcohol solution (2-20 mg / ml) of MAI (CH3NH3I) at 0°C to 80°C (preferably at room temperature) (MAI immersion method). PbI2 and MAI react to form a perovskite compound [(CH3NH3)PbI3(MAPbI3)] as a perovskite layer 44 inside and on the pores of the porous semiconductor 41, and then the porous semiconductor 41 is flooded with a pure isopropyl alcohol solution and dried at 60°C to 120°C (preferably 70°C to 100°C). The mixed cation-mixed halide ((FAPbI3) 1-x (MAPbBr3) x ) type perovskite compounds can be prepared in a similar manner.

[0024] In the above-mentioned manufacturing procedure, the crystal growth of the perovskite compound forming the perovskite layer 44 is controlled in two steps, but this may be done in one step. For example, a perovskite ((CH3NH3)PbI3) solution is permeated into the pores of the porous semiconductor 41 by a spin coating method. Next, toluene is dropped during spinning to precipitate microcrystals and make the surface mirror-finished (poor solvent precipitation method).

[0025] The hole transport material according to this embodiment is prepared as, for example, a chlorobenzene solution of 60 to 90 mg / ml. The solution is dropped onto the perovskite layer 44, and excess solution is removed by spin coating, followed by drying to form the hole transport layer 5. An additive such as TPFB may be added to the hole transport material. When TPFB is added, the TPFB is preferably 0.01% by weight to 100% by weight, and particularly preferably 0.1% by weight to 50% by weight, of the hole transport material. For example, the hole transport material according to this embodiment is weighed out to be 30 mM, and TPFB equivalent to 10% by weight is added thereto, and the resulting solution is dissolved in chlorobenzene to form the hole transport layer 5.

[0026] The above steps from the formation of the PbI2 layer to the formation of the hole transport layer 5 are preferably carried out in a dry nitrogen atmosphere such as in a glove box. Finally, the electrode 6 is formed. The photoelectrode 61 is formed by attaching a thin film of gold or the like to the surface of the blocking layer 3 by a method such as vacuum deposition.

[0027] As described above, in this embodiment, the counter electrode 62 is a carbon electrode using CNT. In this embodiment, a solution (hereinafter also referred to as a CNT solution) in which CNTs, which are an example of solid matter, and a resin binder are dispersed in an isopropyl alcohol solution (hereinafter also referred to as IPA), which is an example of a solvent, is applied to the hole transport layer 5, and then the IPA is evaporated. As a result, the CNTs, which are residues, are dried and turned into a film (hereinafter also referred to as a CNT film), and the counter electrode 62 is formed.

[0028] In the above-mentioned manufacturing method, if the density of CNTs in the CNT solution is increased, the viscosity of the CNT solution increases, so that the thickness of the counter electrode 62 after the IPA is evaporated can be increased, and the resistance of the counter electrode 62 itself can be reduced. On the other hand, if the density of CNTs in the CNT solution is high, air is likely to remain between the counter electrode 62 and the hole transport layer 5 after the IPA is evaporated, so that the contact area between the counter electrode 62 and the hole transport layer 5 is reduced, which is a drawback in that the contact resistance at the boundary between the counter electrode 62 and the hole transport layer 5 increases.

[0029] Conversely, when the density of CNTs in the CNT solution is reduced, the viscosity of the CNT solution is reduced, so that almost no air remains between the counter electrode 62 and the hole transport layer 5 after the IPA is evaporated. This increases the contact area between the counter electrode 62 and the hole transport layer 5, and reduces the contact resistance at the boundary between the counter electrode 62 and the hole transport layer 5. On the other hand, if the viscosity of the CNT solution is low, the thickness of the counter electrode 62 cannot be increased, which is a drawback in that the resistance of the counter electrode 62 itself becomes high.

[0030] Therefore, in this embodiment, multiple types (two types in this embodiment) of CNT solutions with different CNT densities are used, and CNT films formed from the respective CNT solutions are laminated to form the counter electrode 62. Hereinafter, the CNT solution with the lower CNT density will be referred to as the first CNT solution 63a (an example of a viscous material), and the CNT solution with the higher CNT density will be referred to as the second CNT solution 63b (an example of a viscous material).

[0031] First, the first CNT solution 63a is applied to the surface of the hole transport layer 5. Specifically, the first CNT solution 63a is prepared so that the CNTs are 0.4 wt %, the binder, etc. are 0.6 wt %, and the total solid content is 1.0 wt %, and is applied to the surface of the hole transport layer 5 to a thickness of 150 μm. Thereafter, the IPA is evaporated to dry the CNTs. The IPA is evaporated, for example, by heating at 80° C. for 5 minutes. When the IPA is evaporated, the thickness of the residual CNT film is 2 μm, and the density of the CNTs is 0.6 g / cm. 3 Hereinafter, the CNT film formed from the first CNT solution 63a will be referred to as a first CNT film 62a (an example of an electrode layer).

[0032] Next, the second CNT solution 63b is applied to the surface of the first CNT film 62a. Specifically, the second CNT solution 63b, which is prepared so that the CNT is 0.6 wt%, the binder, etc. is 0.9 wt%, and the total solid content is 1.5 wt%, is applied to the surface of the first CNT film 62a to a thickness of 1200 μm. Thereafter, the IPA is evaporated to dry the CNT. When the IPA is evaporated, the thickness of the residual CNT film becomes 12 μm, and the density of the CNT becomes 1.0 g / cm3. Hereinafter, the CNT film formed from the second CNT solution 63b is referred to as the second CNT film 62b (an example of an electrode layer).

[0033] The first CNT solution 63a has a low viscosity due to a low density of the solid content including CNTs, and when the first CNT solution 63a is applied to the hole transport layer 5 and the IPA is evaporated, almost no air remains between the first CNT film 62a and the hole transport layer 5. Therefore, the contact resistance at the boundary between the first CNT film 62a and the hole transport layer 5 can be reduced.

[0034] The second CNT solution 63b has a high viscosity due to the high density of the solid content including CNTs, but the density of CNTs in the second CNT film 62b after application and evaporation of the IPA is high, and the thickness of the second CNT film 62b can be made thicker than that of the first CNT film 62a, so the resistance of the second CNT film itself can be reduced. Since both the first CNT film 62a and the second CNT film 62b are made of CNTs, the contact resistance at the boundary between the first CNT film 62a and the second CNT film 62b is negligible.

[0035] In this way, by forming the counter electrode 62 by stacking the first CNT film 62a and the second CNT film 62b, the film thickness is 14 μm (2 μm+12 μm) and the surface resistivity is 10 Ω / cm 2 In other words, the counter electrode 62 has low contact resistance at the boundary with the hole transport layer 5 and low resistance of the electrode itself.

[0036] Other embodiments (1) In the above embodiment, the counter electrode 62 is formed using the first CNT solution 63a and the second CNT solution 63b, which have the same active material (carbon nanotubes) but different solid content densities, but this is not limited thereto. The counter electrode 62 may be formed by stacking three or more types of CNT films using three or more types of CNT solutions with different solid content densities. In this case, it is preferable that the CNT film closer to the hole transport layer 5 in the stacking direction has a lower solid content density in the CNT solution and a thinner film thickness. In addition, the active material may be carbon nanotubes containing a small amount of impurities, or may be an active material such as graphite, carbon black, acetylene black, or graphene.

[0037] (2) In the above embodiment, IPA is evaporated by heating, but this is not limited to the above. Since IPA is volatile, IPA may be evaporated at room temperature. Although it takes more time to dry the CNT film by evaporating IPA at room temperature, the CNT film becomes denser than when it is dried by heating.

[0038] [Summary of the above embodiment] Hereinafter, in the above-described embodiment, the following configurations are envisioned. <1> One embodiment of the perovskite solar cell (10) is a perovskite solar cell (10) having an electrode (62) provided on the surface of a hole transport layer (5). The electrode (62) is formed by stacking a plurality of electrode layers (62a), (62b), each of which has a different density and is made of the same active material.

[0039] For example, an electrode layer (62a) made of a low-density active material is formed adjacent to the surface of the hole transport layer (5), and a high-density electrode layer (62b) made of the same active material but with a higher density is laminated on the low-density electrode layer (62a) to a greater thickness than the low-density electrode layer (62a) to form an electrode (62). This makes it possible to reduce the contact resistance between the low-density electrode layer (62a) and the hole transport layer (5) and also to reduce the resistance of the electrode (62) itself.

[0040] <2> The active material is preferably carbon nanotubes.

[0041] Carbon nanotubes are highly conductive and are a continuous fibrous body. Because they are a continuous body, the grain boundary area is small and the resistance between the particles is low, so the resistance of the electrode (62) itself can be reduced.

[0042] <3> The electrode (62) is preferably formed so that the electrode layers (62a), (62b) closer to the hole transport layer (5) have a lower density and a thinner thickness.

[0043] An electrode layer (62a) having a low density and a small thickness can reduce the contact resistance with the hole transport layer (5). Furthermore, the resistance of an electrode layer (62b) having a higher density and a larger thickness than an electrode layer (62a) having a low density and a small thickness is smaller than the resistance of the electrode layer (62a) having a low density. For this reason, when the electrode (62) is formed so that the electrode layers (62a) and (62b) closer to the hole transport layer (5) have a lower density and a thinner thickness, the contact resistance with the hole transport layer (5) is smaller, and an electrode (62) having a low overall resistance can be obtained.

[0044] <4> In one embodiment of a method for manufacturing a perovskite solar cell (10), a viscous material (63a), (63b) having solid matter dispersed in a solvent is applied to the surface of a hole transport layer (5) to laminate a plurality of electrode layers (62a), (62b) having different densities, thereby forming an electrode (62).

[0045] By manufacturing the perovskite solar cell (10) using the above-mentioned simple steps, it is possible to obtain an electrode (62) that has low contact resistance with the hole transport layer (5) and low resistance overall.

[0046] <5> The solid matter is preferably carbon nanotubes, and the electrode (62) is preferably formed by repeatedly applying and drying viscous materials (63a), (63b) to laminate a plurality of electrode layers (62a), (62b).

[0047] As described above, by repeating the simple process of applying and drying a plurality of electrode layers (62a), (62b) having different densities, an electrode layer (62a) having a low density and a thin thickness is formed on the surface of the hole transport layer 5, thereby making it possible to reduce the contact resistance with the hole transport layer 5. In addition, by forming an electrode layer (62b) having a high density and a large thickness on an electrode layer (62a) having a low density and a small thickness on the surface of the hole transport layer 5, an electrode (62) having a low resistance overall can be easily obtained. [Industrial Applicability]

[0048] The present invention can be used for a perovskite solar cell and a method for manufacturing the same. [Explanation of symbols]

[0049] 5: hole transport layer, 10: perovskite solar cell, 62: counter electrode (electrode), 62a: first CNT film (electrode layer), 62b: second CNT film (electrode layer), 63a: first CNT solution (viscous material), 63b: second CNT solution (viscous material)

Claims

1. A perovskite solar cell comprising an electrode provided on a surface of a hole transport layer, The electrode is formed by stacking a plurality of electrode layers, A perovskite solar cell, wherein each of the plurality of electrode layers has a different density but is made of the same active material.

2. The perovskite solar cell according to claim 1 , wherein the active material is a carbon nanotube.

3. 3. The perovskite solar cell according to claim 1, wherein the electrodes are formed so that the electrode layers closer to the hole transport layer have a lower density and a thinner thickness.

4. A manufacturing method for perovskite solar cells in which electrodes are formed by stacking multiple electrode layers with different densities on the surface of a hole transport layer by applying a viscous material in which solids are dispersed in a solvent.

5. the solid material is a carbon nanotube; The method for manufacturing a perovskite solar cell according to claim 4 , wherein the electrodes are formed by stacking a plurality of the electrode layers by repeatedly applying and drying the viscous material.

Citation Information

Patent Citations

  • Manufacture of solar battery and its electrode

    JP1999330506A